Estimation of thermodynamic properties and ionic equilibria of cobalt chloride solution at 298 K - Lee, MS; Oh, YJ (JAPAN INST METALS, 2004)
We developed a chemical model to analyze ionic equilibria in a cobalt chloride solution at 298 K. The chemical model consisted of chemical equilibria. mass and charge balance equations. The activity coefficients Of Solutes and water activity were calculated with Bromley equation. Values of the equilibrium constants for the formation of cobalt chloride complexes at zero ionic strength and of the interaction parameters were estimated by applying Bromley equation to the reported equilibrium constants at different ionic strength. The effect of CoCl2 and HCl concentrations on the distribution of cobalt species was obtained. The predicted pH values for CoCl2-HCl-NaOH-H2O system agreed well with those measured at 298 K.
Keywords: MODIFIED BROMLEYS METHODOLOGY; SODIUM-SALTS; SEPARATION; NICKEL(II); D2EHPA